(untitled) (Journal of Dhaka National Medical College & Hospital, 2015)
Background: Subarachnoid block in selected cases is a safer alternative to general anaesthesia for laparoscopic cholecystectomy because of advantages of neuraxial block over general anaesthesia. Objective: The aim of study is to compare the outcome of patients between subarachnoid block and general anaesthesia for laparoscopic cholecystectomy. Methods: Sixty patients aged 20-50 years of ASA grade I & II for laparoscopic cholecystectomy under spinal and general anaesthesia were randomly selected equally into two groups: SA group: Spinal Aneasthesia group (n=30) GA Group: General anaesthesia group (n=30) Using CO2 pneumoperitoneum intra-abdominal pressure in SA group was kept at 10mmHg (Low) while in GA group was at 15mmHg (High). All patients in SA group were sedated after adequate block (T5). Parametric data like pulse and blood pressure were analyzed by ANOVA test & nonparametric data like abdominal discomfort, right shoulder pain, nausea, vomiting were analyzed by chi-square test. Results: The study revealed that one patient in SA group required conversion to GA. Per operatively in SA group hypotension was recorded in 10% of patients while in GA group it was 6.6%. On the other hand In SA group 10% of patients had vomiting, 10% experienced right shoulder pain. Postoperatively in GA group 20% of patients had vomiting, 10% of patients had right shoulder pain and 90% patients required injectable analgesics in the immediate postoperative period. On the other hand in SA group no patient had right shoulder pain, 3.3% of patients had vomiting, 6.6% of patients had post dural puncture headache. Average time of stay in hospital in both groups was 1.9 days. Conclusion: It can be concluded that laparoscopic cholecystectomy under SA with low pressure CO2 pneumoperitoneum is a safer alternative to GA because there is no intubation related airway morbidity & mortality,optimum muscle relaxation,decreased surgical bed oozing, economical, pain free early postoperative period, more rapid return of gut function and decreased postoperative nausea & vomiting. J. Dhaka National Med. Coll. Hos. 2015; 21 (02): 38-41